Real estate market and the structuring of space: inform al settlements in curitiba metropolitan zone (2009)
The text presents preliminary results of the research done by LAURB - UFPR, which intends, as one of its goals, to analyze the role’of the informal land market in the formation of the metropolitan area of Curitiba. First, the different phases of organization of that market are presented, considering the formation process of the metropolitan set. Then, the legal and ilegal uses of the land, and the capitalist production of the city are put side by side, to show the logical organization of the land market as responsible for the growth of the irregular settlements in the city. Finally, it demonstrates that the real estate business inside irregular areas is a common practice, which follows the same patterns found in the formal land market.